2017
DOI: 10.1021/acs.jpcc.7b02254
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics Investigations of Sr/Ca-Doped LaPO4 Proton Conductors

Abstract: Proton conductors loom out of the pool of candidate materials with great potential to boost hydrogen alternatives to fossil-based resources for energy. Acceptor-doped lanthanum orthophosphates are considered for solid oxide fuel cells (SOFCs) for their potential stability and conductivity at high temperature. By exploring the crystal and defect structure of x% Sr/Ca-doped LaPO 4 with different nominal Sr/Ca concentrations (x = 0−10) with neutron powder diffraction (NPD) and X-ray powder diffraction (XRD), we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The small absorption peaks next to the asymmetric stretching vibration peaks at 1198.37 and 1207.05 cm –1 are interpreted as the contribution of a fraction of electrons to the P–O vibrations from the small and highly charged zirconium cations polarizing the P–O band . It can be observed that the absorption band representing the asymmetric stretching vibration of PO 4 is wider in the FTIR spectrum of the treated material than the FTIR spectrum of the original sample, which is due to the increase in bond length in the P–O–H vibration and is related to the presence of protons . Furthermore, the weak absorption peak around 3400 cm –1 represents the stretching vibration of −OH. Li 2.5 Sr 0.75 Zr 1.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The small absorption peaks next to the asymmetric stretching vibration peaks at 1198.37 and 1207.05 cm –1 are interpreted as the contribution of a fraction of electrons to the P–O vibrations from the small and highly charged zirconium cations polarizing the P–O band . It can be observed that the absorption band representing the asymmetric stretching vibration of PO 4 is wider in the FTIR spectrum of the treated material than the FTIR spectrum of the original sample, which is due to the increase in bond length in the P–O–H vibration and is related to the presence of protons . Furthermore, the weak absorption peak around 3400 cm –1 represents the stretching vibration of −OH. Li 2.5 Sr 0.75 Zr 1.…”
Section: Resultsmentioning
confidence: 96%
“…57 It can be observed that the absorption band representing the asymmetric stretching vibration of PO 4 is wider in the FTIR spectrum of the treated material than the FTIR spectrum of the original sample, which is due to the increase in bond length in the P−O−H vibration and is related to the presence of protons. 58 Furthermore, the weak absorption peak around 3400 cm −1 represents the stretching vibration of −OH. 59−61 Li 2.5 Sr 0.75 Zr 1.…”
Section: Proton Conduction Proofmentioning
confidence: 99%